SOSIALISASI MUTU PELAYANAN KELUARGA BENCANA TERHADAP PENINGKATAN AKSEPTOR KB DAN STATUS GIZI ANAK PADA MASA PANDEMI COVID-19 DI PUSKESMAS BANDAR DURIAN KABUPATEN LABUHAN BATU UTARA - Riza Siregar; Elmina Tampubolon; Novrika Silalahi (INSTITUT KESEHATAN DELI HUSADA, 2022)
This study aims to analyze the quality of family planning services during the Covid-19 pandemic to increase family planning acceptors and children's nutritional status at the Bandar Durian Health Center. This study uses quantitative research methods with the number of respondents 90 women of childbearing age who have toddlers. The results of the study concluded that the quality of family planning services during the Covid-19 pandemic at the Bandar Durian Health Center was very good, the results of the analysis of the quality of family planning services had a significant effect on increasing family planning acceptors and children's nutritional status. It is hoped that the Bandar Durian Health Center will improve the quality of family planning services by always paying attention to the completeness of infrastructure, providing quality counseling to patients, always being responsive and thorough in providing family planning services, increasing the competence of health workers and officers to be polite and friendly in providing family planning services.